Two-atom collisions and the loading of atoms in microtraps - Yin H. Fung (2018)
We review light assisted collisions in a high-density far-off resonant optical trap (FORT). By tuning the parameters of the light that induces the collisions, the effects of the collisions can be controlled. Trap loss can be suppressed even at high atomic densities, allowing us to count the atoms using fluorescence detection. When only two atoms are trapped, individual loss events reveal new information about the process, and the simplicity of the system allows for a numerical simulation of the dynamics. By optimizing the experimental parameters, we implement an efficient method to prepare single atoms in the FORT. Our methods can be extended to load quantum registers for quantum information processing. © 2014 by the authors: licensee MDPI, Basel, Switzerland.